Peran organisasi Islam internal Universitas dalam realisasi pembelajaran agama - Musti'ah, Musti'ah (Institut Agama Islam Negeri (IAIN) Kudus, 2019)
AbstractThe role of Islamic student association of University in the realization of religious learning. In recent years, issues related to the role of internal campus association (ICA) are increasingly being discussed in parts of the worlds. This research aims to examine the role of Islamic internal organization of University in the realization of religious learning. This study employed mixed method. Data were collected using questionnaire to 62 form 342 students, and semi-structured interview with and document (e) the research findings revealed students’ ability on Qur’an reading was weak before joining BBQ program and there was improvement of reading Qur’an ability after they followed the program. The findings also indicated that BBQ program was effective to mediate students in learning to read Qur’an.Keywords: Indonesia, Islamic student association, Muslims, university.